CLIMATE CHANGE ADAPTATION STRATEGIES IN HAJJ MANAGEMENT: A ZERO-CARBON FRAMEWORK USING ECOLOGICAL MODERNIZATION THEORY AND TRIPLE BOTTOM LINE ANALYSIS - Abdillah; Ahmad; Muchriady Muchran (Multazam : Jurnal Manajemen Haji dan Umrah, 2026)
The Hajj pilgrimage, one of the world’s largest annual mass gatherings, generates a substantial carbon footprint while facing increasing climate-related risks, particularly extreme heat stress in Makkah. This study aims to develop a zero-carbon framework for Hajj management based on Ecological Modernization Theory (EMT) and Triple Bottom Line (TBL) analysis. A mixed-methods approach was employed using Life Cycle Assessment (LCA), GHG Protocol modelling, time-series ARDL analysis, semi-structured interviews, and an online survey involving pilgrims and stakeholders. Data were obtained from secondary sources, including reports from the Saudi Ministry of Hajj, UNEP, and IPCC, as well as primary data collected through interviews and surveys. The findings indicate that Hajj-related emissions currently exceed 1.8 million tons CO₂e per season, with international aviation contributing the largest share. Under a Business-as-Usual scenario, emissions could surpass 5 million tons CO₂e by 2030. The proposed framework integrates renewable energy, electrified mass transportation, circular ihram recycling, and carbon offsetting to significantly reduce emissions while improving pilgrim safety. The study concludes that a zero-carbon Hajj is achievable through coordinated environmental, social, and economic strategies aligned with Saudi Vision 2030 and the Saudi Green Initiative.